Utilizing the Quizizz Application to Improve Students’ Vocabulary Mastery at Senior High School - Frisca Oktaviany; Sujarwo; Muhamad Yahrif (CV. Eureka Murakabi Abadi, 2026)
This study aims to determine how effective the Quizizz application is in increasing student vocabulary at SMA Negeri 23 Makassar. This study used a quasi-experimental method. Two classes were selected as samples: one experimental class that used Quizizz to teach vocabulary and one control class that used conventional methods. Pre-test, post-test, and questionnaire were used in this study. Data were analyzed using descriptive and inferential statistics using the SPSS 25 program. The results showed a significant increase in students' vocabulary mastery in the experimental class compared to the control class. The average score of the experimental group increased from 58.42 in the pre-test to 87.67 in the post-test. Meanwhile, the control class increased from 57.61 to 66.33. Findings from the independent t-test showed a significant difference between the post-test scores of both groups (sig. <0,05), which confirmed the effectiveness of Quizizz as an interactive learning medium. In conclusion, Quizizz app contributed positively in improving students’ vocabulary mastery and engagement in English learning.